New record of the species \( Clarkus sheri\) (Mulvey, 1967a) Jairajpuri, 1970 (Mononchida: Mononchidae) in Vietnam - Thanh Tam, Vu Thi; Mai Linh, Le Thi; Dinh Tu, Nguyen (Academia Journal of Biology, 2022)
The genus Clarkus with a redescription of Clarkus sheri females is recorded and illustrated for the first time in Vietnam. Eight females of Clarkus sheri were collected from several natural reserves: Bac Me (Ha Giang province), Van Ban (Lao Cai province), Vu Quang (Ha Tinh province), Kon Chu Rang (Gia Lai province) and Me Linh (Vinh Phuc province). Their measurements and features corresponded well with the type population from California, USA and other populations from South Africa, Mexico, Japan and India.